A glory of unicorns - Coville, Bruce; Berenzy, Alix (Scholastic, 1998)
Thirteen short stories, by such authors as Nancy Varian Berberick, Gregory Maguire, and Margaret Bechard, about unicorns in both mythical and contemporary settings.